Labiobaetis Novikova & Kluge in Borneo (Ephemeroptera, Baetidae) - Kaltenbach, Thomas (Zookeys, 2020)
Abstract. Material collected between 2000 and 2014 on the island Borneo, including the Indonesian province of Kalimantan, the Malaysian province of Sabah and Brunei Darussalam, substantially increased our knowledge of Labiobaetis on this island. The total number of Labiobaetis species in Borneo increased to five, as only one species, L. borneoensis (Müller-Liebenau, 1984), was previously reported. Three new species were identified by morphology and partly by using genetic distance (COI, Kimura 2-parameter). They are described and illustrated based on their larvae (Labiobaetis bakerae sp. nov., L. penan sp. nov. and L. dayakorum sp. nov.); in one case, the imago is described as well. New reports of L. borneoensis are presented and the imago of this species is described for the first time. Labiobaetis moriharai (Müller-Liebenau, 1984), originally described from mainland Malaysia (Province Selangor), is reported from Borneo for the first time. The interspecific K2P distances in Borneo are between 19% and 25%, the intraspecific distances are usually between 0% and 1%. The total number of Labiobaetis species worldwide is augmented to 126.